Fatigue Life Assessment of Orthotropic Steel Deck with UHPC Pavement - Xu Jiang; Yuan Yuan; Chong Wu; Chengwei Luo (Journal of Engineering)
In recent years, a number of large-span bridges with orthotropic steel decks were constructed in China. With increasing traffic volumes and higher wheel loads, many fatigue cracks developed at the welds and the edge of cut-out holes. This paper aims at presenting the numerical analysis on the fatigue performance of the orthotropic steel deck using ultrahigh performance concrete (UHPC) overlay as the deck pavement instead of the conventional asphalt concrete pavement. By using finite element method (FEM) model, stress distribution at fatigue sensitive locations under the action of wheel loads is characterized and the obtained stress ranges indicate that the UHPC pavement significantly reduces the magnitude of the stress peak valued. A suggested truck stream model based on the weigh-in-motion (WIM) data of four bridges in China is employed to calculate the stress variation at specific fatigue details. Furthermore, the fatigue damage accumulation at fatigue details under the UHPC and conventional asphalt concrete pavement is studied based on Miner’s linear cumulative damage rule and the rain-flow method. The results indicate that the UHPC pavement on the orthotropic steel deck can extend the service lives of the concerned regions over 100 years, but the fatigue lives will reduce significantly when the elastic modulus of UHPC decreases to 50% of the original value.